2013
DOI: 10.1016/j.bbamcr.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

ARF1-regulated coatomer directs the steady-state localization of protein kinase C epsilon at the Golgi apparatus

Abstract: Protein kinase C epsilon (PKCε) contributes to multiple signaling pathways affecting human disease. The function of PKCε requires it to undergo changes in subcellular distribution in response to signaling events. While the mechanisms underlying this translocation are incompletely understood it involves the receptor for activated C kinase protein (RACK2/β′-COP). This receptor also functions as a vesicle coat protein in the secretory pathway where it is regulated by the small GTP-binding protein ADP-ribosylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although the technique commonly employed is relatively crude (the membrane fraction includes all membranous organelles and the plasma membrane), it may be further refined in the future. It is interesting to note that cell-based studies have implicated the Golgi, mitochondrion, and plasma membrane as sites of PKCε translocation [62]. A final important consideration for the DAG-PKCε hypothesis is that triglyceride hydrolysis by ATGL in the hepatocyte preferentially produces sn -1,3-DAG, which is incapable of activating PKC [63,64].…”
Section: Diacylglycerol In Hepatic Insulin Resistancementioning
confidence: 99%
“…Although the technique commonly employed is relatively crude (the membrane fraction includes all membranous organelles and the plasma membrane), it may be further refined in the future. It is interesting to note that cell-based studies have implicated the Golgi, mitochondrion, and plasma membrane as sites of PKCε translocation [62]. A final important consideration for the DAG-PKCε hypothesis is that triglyceride hydrolysis by ATGL in the hepatocyte preferentially produces sn -1,3-DAG, which is incapable of activating PKC [63,64].…”
Section: Diacylglycerol In Hepatic Insulin Resistancementioning
confidence: 99%
“…A recent study reported the PKCε-RACKε-β′-COP complex to travel to the GA via a small GTP-binding protein ADP-ribosylation factor (ARF-1)-mediated pathway in NIH3T3 cells in an unstimulated state. The same study also reported that phorbol ester-dependent transport of PKCε-RACKε to the membrane surface is coatomer independent (Peterson and Stamnes, 2013 ), suggesting that the role of the coatomer in PKCε transportation pertains to the Golgi alone.…”
Section: Chauffeur For Pkcεmentioning
confidence: 83%
“…The coatomer protein complex (COP) is required for budding from Golgi membranes and is essential for the retrograde Golgi-to-ER transport of dilysine-tagged proteins. The complex also influences the Golgi structural integrity, as well as the processing, activity and endocytic recycling of LDL (low-density lipoprotein) receptors [ 66 ]. It is involved in the Golgi disassembly and reassembly processes during the cell cycle and in autophagy by playing a role in an early endosome function [ 65 ].…”
Section: Resultsmentioning
confidence: 99%